Molecular genetic analysis of 103 sporadic colorectal tumours in Czech patients - Vasovcak, Peter; Pavlikova, Kristyna; Sedlacek, Zdenek; Skapa, Petr; Kouda, Martin; Hoch, Jiri; Krepelova, Anna (PloS one, 2011)
The Czech Republic has one of the highest incidences of colorectal cancer (CRC) in Europe. To evaluate whether sporadic CRCs in Czech patients have specific mutational profiles we analysed somatic genetic changes in known CRC genes (APC, KRAS, TP53, CTNNB1, MUTYH and BRAF, loss of heterozygosity (LOH) at the APC locus, microsatellite instability (MSI), and methylation of the MLH1 promoter) in 103 tumours from 102 individuals. The most frequently mutated gene was APC (68.9% of tumours), followed by KRAS (31.1%), TP53 (27.2%), BRAF (8.7%) and CTNNB1 (1.9%). Heterozygous germline MUTYH mutations in 2 patients were unlikely to contribute to the development of their CRCs. LOH at the APC locus was found in 34.3% of tumours, MSI in 24.3% and MLH1 methylation in 12.7%. Seven tumours (6.9%) were without any changes in the genes tested. The analysis yielded several findings possibly specific for the Czech cohort. Somatic APC mutations did not cluster in the mutation cluster region (MCR). Tumours with MSI but no MLH1 methylation showed earlier onset and more severe mutational profiles compared to MSI tumours with MLH1 methylation. TP53 mutations were predominantly located outside the hot spots, and transitions were underrepresented. Our analysis supports the observation that germline MUTYH mutations are rare in Czech individuals with sporadic CRCs. Our findings suggest the influence of specific ethnic genetic factors and/or lifestyle and dietary habits typical for the Czech population on the development of these cancers.
Keywords: protein familiární adenomatózní polypózy; ztráta heterozygozity; Humans; mikrosatelitní nestabilita; Promoter Regions, Genetic; lidé středního věku; MutL Protein Homolog 1; běloši; DNA-glykosylasy; beta-katenin; Proto-Oncogene Proteins B-raf; Microsatellite Instability; nádorový supresorový protein p53; zárodečné mutace; Female; Aged; mladý dospělý; adaptorové proteiny signální transdukční; dospělí; ras Proteins; Loss of Heterozygosity; White People; jaderné proteiny; senioři; lidé; Adaptor Proteins, Signal Transducing; protoonkogenní proteiny p21(ras); DNA Glycosylases; MutL homolog 1; protoonkogenní proteiny; Adult; Adenomatous Polyposis Coli Protein; DNA Methylation; protoonkogenní proteiny B-Raf; metylace DNA; Germ-Line Mutation; ženské pohlaví; kolorektální nádory; Male; Middle Aged; Proto-Oncogene Proteins p21(ras); Adolescent; Nuclear Proteins; Czech Republic; Aged, 80 and over; Proto-Oncogene Proteins; beta Catenin; Young Adult; Ras proteiny; senioři nad 80 let; Česká republika; mužské pohlaví; promotorové oblasti (genetika); Colorectal Neoplasms; mladiství; Tumor Suppressor Protein p53